The Costs of Tax Compliance in Armenia - World Bank Group (International Finance Corporation, Yerevan, 2017)
The report represents the main results of IFC's 2010 survey of private sector companies and individual entrepreneurs in Armenia. Its findings evaluate the cost of compliance with tax legislation and supervisory bodies to fulfill tax liabilities by legal entities (companies) and individual entrepreneurs in 2009. The survey report examines the cost of tax compliance in terms of time and money. The number of man hours spent working on tax compliance can also be expressed in terms of money, as the cost to businesses includes staff wages as well as any lost productivity. Thus, from the business' perspective, the time required to comply with tax regulation is an additional cost associated with paying taxes. The study shows that tax compliance in Armenia is a burden on private businesses, especially for small companies and individual entrepreneurs, which spend an additional 10 percent of income on tax administration. Despite the fact that most survey respondents reported that the quantity of taxes is the main concern for Armenian businesses (39), other characteristics of the tax system - such as tax inspections, corruption associated with paying taxes, tax accounting procedures, tax reports and frequency of filing - are also worrisome for a lot of taxpayers. Therefore, the survey focused on assessment costs of tax compliance and particularly on those that are the costliest and problematic for Armenian business, such as maintaining book of registration of revenues, tax inspections and book of shipment of inventory holdings.